Peran Perbankan Syariah Dalam Mengimplementasikan Keuangan Inklusif Di Indonesia - Suryadi Syabatullah; M. Irwan Padli Nasution (Islamic Education Journal, 2022)
This study aims to analyze the role of Islamic banking in implementing financial inclusion in Indonesia. Financial inclusion is a process to provide access to formal finance for the poor and low income (unbankable people). This study used a qualitative and quantitative approach (mixed research). Qualitative data analysis uses an analytical technique developed by Straruss and Corbin with three major steps, namely open coding, axial coding, and selective coding. Quantitative data analysis uses comparative analysis of financial statements in 2010-2014 and analysis of financial ratios in the form of CAR, ROA, ROE, NPF, and FDR. This research proves that Islamic banking has great potential in implementing financial inclusion, as indicated by significant growth in funding and financing in 2010-2014 and the results of financial ratio analysis also show good performance and financial condition of Islamic banking.